2022
DOI: 10.2106/jbjs.21.01061
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Understanding of Culture-Negative Periprosthetic Joint Infection with Next-Generation Sequencing

Abstract: Background:The challenges of culture-negative periprosthetic joint infection (PJI) have led to the emergence of molecular methods of pathogen identification, including next-generation sequencing (NGS). While its increased sensitivity compared with traditional culture techniques is well documented, it is not fully known which organisms could be expected to be detected with use of NGS. The aim of this study was to describe the NGS profile of culture-negative PJI.Methods:Patients undergoing revision hip or knee a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 25 publications
(39 reference statements)
0
20
0
Order By: Relevance
“…In this multicentre prospective study from across the USA , the authors enrolled 301 patients who met the criteria for PJI diagnosis, with negative cultures seen in 85 patients (28.2%). 1 The major positive finding of this study is that NGS was able to identify an organism in 56 of the 85 culture-negative patients (65.9%), with the highest yield of positive results being from tissue sampling (46.6%) followed by swabs (34.1%) and synovial fluid (19.3%). The authors were able to identify 176 different organisms in this cohort, with over 90% being considered uncommon or atypical organisms for PJI.…”
Section: Understanding Culture-negative Periprosthetic Joint Infectionmentioning
confidence: 64%
“…In this multicentre prospective study from across the USA , the authors enrolled 301 patients who met the criteria for PJI diagnosis, with negative cultures seen in 85 patients (28.2%). 1 The major positive finding of this study is that NGS was able to identify an organism in 56 of the 85 culture-negative patients (65.9%), with the highest yield of positive results being from tissue sampling (46.6%) followed by swabs (34.1%) and synovial fluid (19.3%). The authors were able to identify 176 different organisms in this cohort, with over 90% being considered uncommon or atypical organisms for PJI.…”
Section: Understanding Culture-negative Periprosthetic Joint Infectionmentioning
confidence: 64%
“…According to certain researchers, negative reimplantation results are linked to positive reimplantation cultures. In contrast, only one of the five reimplantation cases that tested positive for culture in the study failed [36] .…”
Section: Management Prospectsmentioning
confidence: 79%
“…Over the implant's lifetime, longer prosthesis indwelling duration is linked to a higher overall risk for hematogenous infections. Even persistent illnesses that would have gone unnoticed in the past are now found thanks to the advancement of sophisticated detection techniques for microbial biofilms [2,3] . The management of PJI necessitates sophisticated therapeutic approaches, such as numerous surgical revisions and protracted antimicrobial therapy.…”
Section: Introductionmentioning
confidence: 99%
“…No test offers great sensibility or specificity for diagnosing PJI. The diagnosis of PJI is based on a combination of clinical findings, laboratory evaluation of blood and synovial fluid, and intraoperative findings [ 97 ]. The gold standard remains articular fluid aspiration and culture.…”
Section: Complicationsmentioning
confidence: 99%
“…A recent study showed that almost 30% of PJI were culture-negative after intra-operative sampling. In those cases, next-generation sequencing showed infection in 66% of the cases, which was polymicrobial in 91% [ 97 ]. Blood tests are often negative and should not be mistaken for aseptic loosening before articular fluid analysis [ 97 ].…”
Section: Complicationsmentioning
confidence: 99%